LEGAL POLICY AGRARIA (PERTANAHAN) DI INDONESIA - Savitri, Miya (JURNAL KONSTITUSI, 2011)
Political law is the policy of the law from the Government that will be or have been implemented nationally and have a significant influence on the development or direction of applicable law in a country. The existence and development of agrarian politics and the law can not be separated from macroeconomic policy of the Authority. This is understandable, given the economic problems in one country would be associated with land issues. The development of agrarian laws in Indonesia, can be seen in 4 (four) stages, namely stage of Indonesia before independence (colonial period), stage Era Governance Sukarno, Suharto era, and the stages in the reform period.Â